Mali : Third Review Under the Three-Year Arrangement Under the Extended Credit Facility and Request for a Modification of Performance Criteria; Staff Report; Joint IMF/IDA Debt Sustainability Analysis; Press Release; and Statement by the Executive Director for Mali. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This paper discusses key findings of the Third Review Under the Extended Credit Facility (ECF) for Mali. Implementation of the ECF-supported program has been challenged by the global financial crisis and the ensuing global slowdown. The new program aims to continue prudent fiscal policies and complementary reforms. The 2008 food and oil crisis challenged program implementation, but performance was broadly satisfactory. On the basis of the authorities' satisfactory record, IMF staff recommends completion of the Third Review of the current ECF arrangement.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet